Dysregulated RBM24 phosphorylation impairs APOE translation underlying psychological stress-induced cardiovascular disease - He Yang; Lei Sun; Xuemei Bai; Bingcheng Cai; Zepeng Tu; Chen Fang; Yusheng Bian; Xiaoyu Zhang; Xudong Han; Dayin Lv; Chi Zhang; Bo Li; et al. (Nature Communications)
Abstract Psychological stress contributes to cardiovascular disease (CVD) and sudden cardiac death, yet its molecular basis remains obscure. RNA binding protein RBM24 plays a critical role in cardiac development, rhythm regulation, and cellular stress. Here, we show that psychological stress activates RBM24 S181 phosphorylation through eIF4E2-GSK3β signaling, which causally links psychological stress to CVD by promoting APOE translation (apolipoprotein E). Using an Rbm24 S181A KI mouse model, we show that impaired S181 phosphorylation leads to cardiac contractile dysfunction, atrial fibrillation, dyslipidemia, reduced muscle strength, behavioral abnormalities, and sudden death under acute and chronic psychological stressors. The impaired S181 phosphorylation of RBM24 inhibits cardiac translation, including APOE translation. Notably, cardiomyocyte-specific expression of APOE rescues cardiac electrophysiological abnormalities and contractile dysfunction, through preventing ROS stress and mitochondrial dysfunction. Moreover, RBM24-S181 phosphorylation acts as a serum marker for chronic stress in human. These results provide a functional link between RBM24 phosphorylation, eIF4E-regulated APOE translation, and psychological-stress-induced CVD.